ABCA7 and the altered lipidostasis hypothesis of Alzheimer's disease - Lyssenko, Nicholas N. (Alzheimers Dement, 2020)
We propose the altered lipidostasis hypothesis of Alzheimer's disease (AD). It holds that vulnerable neurons of the entorhinal region generate a neurodegenerative lipid during normal function, adenosine triphosphate–binding cassette transporter subfamily A member 7 (ABCA7) protects from AD pathogenesis by removing it out of the cell, generation of the lipid increases with age, and the minimal amount of ABCA7 needed to dispose of the rising volumes of the lipid also increases with age. A survey of ABCA7 protein levels in the hippocampus or parietal cortex of 123 individuals with or without AD neuropathology showed that individuals with low ABCA7 developed AD neuropathology at a younger age, those with intermediate ABCA7 developed it later, and individuals who developed it very late had high ABCA7, the same as the youngest controls. ABC transporters closely similar to ABCA7 protect cells by removing toxic lipids. ABCA7 may have analogous functions. The hypothesis predicts lipidosis and membrane protein dysfunction in neurons with low ABCA7. Further work will identify the neurodegenerative lipid and determine approaches to exploit ABCA7 for therapeutic purposes.